Shelled Pteropod individual-based model output for the publication: The impact of aragonite saturation variability on shelled pteropods: An attribution study in the California current system ... - Hofmann Elizondo, Urs; Vogt, Meike; Bednaršek, Nina; Münnich, Matthias; Gruber, Nicolas (Dryad, 2025)
Observations from the California Current System (CalCS) indicate that the long-term trend in ocean acidification (OA) and the naturally occurring corrosive conditions for the CaCO3 mineral aragonite (saturation state Ω < 1) have a damaging effect on shelled pteropods, a keystone group of calcifying organisms in the CalCS. Concern is heightened by recent findings suggesting that shell formation and developmental progress are already impacted when Ω falls below 1.5. Here, we quantify the impact of low Ω conditions on pteropods using an individual-based model (IBM) with life-stage-specific mortality, growth, and behaviour in a high-resolution regional hindcast simulation of the CalCS between 1984 and 2019. Special attention is paid to attributing this impact to different processes that lead to such low Ω conditions, namely natural variability, long-term trend, and extreme events. We find that much of the observed damage in the CalCS, and specifically >70% of the shell CaCO3 loss, is due to the pteropods’ ... : This dataset contains the modelled trajectories of shelled pteropod in the California Current System for each year in the period between 1984 and 2019. The population dynamics were modelled using an extended version of the shelled pteropod Individual-Based Model (spIBM). The environmental conditions experienced by the modelled pteropods and their movement were calculated using the Lagrangian tool OceanParcelsv2.1.3 and the biogeochemical-physical forcing taken from the high-resolution hindcast simulation of the Northeast Pacific taken from Desmet et al. (2022). The spIBM is parameterized based on members of the Limacinidae family, and calibrated to capture the observed pteropod abundance signal, life-stage duration, and succession sequence for the temperate region. It simulates the pteropod life-cycle using four life-stages (eggs, larvae, juveniles, and adults) across two generations per year (spring and overwintering generation). The pteropod population is simulated from January 1st to December 31st at a ...